Rearrangement of beta,gamma-unsaturated esters with thallium trinitrate: synthesis of indans bearing a beta-keto ester moiety - Silva Jr. Luiz F.; Pedrozo Eliane C.; Ferraz Helena M. C. (Journal of the Brazilian Chemical Society, 2006)
The rearrangement of beta,gamma-unsaturated esters, such as 2-(3,4-dihydronaphthalen-1-yl)-propionic acid ethyl ester, with thallium trinitrate (TTN) in acetic acid leads to 3-indan-1-yl-2-methyl-3-oxo-propionic acid ethyl ester in good yield, through a ring contraction reaction. The new indans thus obtained feature a beta-keto ester moiety, which would be useful for further functionalization.